Model Pembelajaran Problem Beased Learning (PBL) Menggunakan Kartu Bridge Terhadap Hasil Belajar Siswa Pada Materi Peluang - astriani, betri; Indrayati, Helni; domi, domi (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
The formulation of the problem in this study is "Is the Problem Beased Learning (PBL) Learning Model Using Bridge Cards Effectively Against Student Learning Outcomes in Class VIII Opportunity Materials in Pagaralam 2 Public Middle School Academic Year 2018/2019?". The purpose of this study was to determine the effectiveness of Problem Beased Learning (PBL) Learning Models Using Bridge Cards Against Student Learning Outcomes in Opportunity Materials in Class VIII of Pagaralam 2 Public Middle School Academic Year 2018/2019. The research method is the experimental method with the design of the pretest-posttest control group design. The sample of this study is class VIII E as the experimental class with the number of students that is 31 and that is 70.67 while the sample in the control class class VIII H with the number of students is 31 and that is 60.64. Data collection techniques used documentation and tests. The data analysis technique uses the t test. In the experimental class with a value of 70.67 and S which is 13.00 while in the control class that is 60.64 and S is 13.52, it is obtained tcount 3.1206 t table 1.701, then Ho is rejected Ha is accepted, meaning the research hypothesis is accepted. So Problem Beased Learning (PBL) Learning Model Using Bridge Cards Effectively Against Student Learning Outcomes In Opportunity Materials In Class VIII Pagaralam 2 Public Middle School Academic Year 2018/2019